Working memory in action: Transsaccadic working memory deficits in the left visual field and after transcallosal remapping. (February 2023) - Moussaoui, Simar; Pereira, Christina F.; Niemeier, Matthias
Abstract: Every waking second, we make three saccadic eye movements that move our retinal images. Thus, to attain a coherent image of the world we need to remember visuo-spatial information across saccades. But transsaccadic working memory (tWM) remains poorly understood. Crucially, there has been a debate whether there are any differences in tWM for the left vs. right visual field and depending on saccade direction. However, previous studies have probed tWM with minimal loads whereas spatial differences might arise with higher loads. Here we employed a task that probed higher memory load for spatial information in the left and right visual field and with horizontal as well as vertical saccades. We captured several measures of precision and accuracy of performance that, when submitted to principal component analysis, produced two components. Component 1, mainly associated with precision, yielded greater error for the left than the right visual field. Component 2 was associated with performance accuracy and unexpectedly produced a disadvantage after rightward saccades. Both components showed that performance was worse when rightward or leftward saccades afforded a shift of memory representations between visual fields compared to remapping within the same field. Our study offers several novel findings. It is the first to show that tWM involves at least two components likely reflecting working memory capacity and strategic aspects of working memory, respectively. Reduced capacity for the left, rather than the right visual field is consistent with how the left and right visual fields are known to be represented in the two hemispheres. Remapping difficulties between visual fields is consistent with the limited information transfer across the corpus callosum. Finally, the impact of rightward saccades on working memory might be due to greater interference of the accompanying shifts of attention. Our results highlight the dynamic nature of transsaccadic working memory.